Appraisal of certain linear and nonlinear k-ε turbulence models - Mandal S.; Bhargava P.; Ojha C.S.P. (My University, 2025)
To simulate wind flow around bluff bodies, a large number of turbulence models have been proposed in the literature. Basically, these models can be classified into two categories, i.e., linear and nonlinear models. Such a classification is often used to interpret the possible interrelationship for stresses and strains within a flow field. Thus, it is expected that linear turbulence models should reflect a linear relationship between stresses and strains. In case of nonlinear models, attempts have been made to introduce more and more higher order terms in the linear models to enhance their nonlinear characteristics. Present study analyses a flow field data to ascertain the behaviour of linear and nonlinear models in terms of the stress and strain response. As the production and destruction terms in turbulence closure models also depend on a stress term, it also looks into the variations of production and destruction terms in turbulent transport equations in different zones of the turbulent flow field. Here, the variations of these terms have been also examined using linear and nonlinear turbulence models and the variations of these terms are linked with inherent nonlinearity in the turbulent models. To support the analysis, the stress strain relationship based on continuum approach has also been scrutinized using the data. Copyright © 2013 APCWE-VIII. All rights reserved. Published by Research Publishing, Singapore.